Status of Price Variations of Fish, Livestock and Poultry Products: A Case Study in Gazipur District of Bangladesh (Annals of Bangladesh Agriculture, 2021)
This study examined the pattern of price variations of major fish, livestock and poultry products in Gazipur district of Bangladesh. The secondary data on the average wholesale and retail prices of ten important commodities for a period of six years (June 2014 to June 2019) were collected from the Department of Agricultural Marketing (DAM) under the Ministry of Agriculture of the Government. The averages were calculated from a total of 1900 wholesalers and 2450 retailers in Gazipur district. Polynomial trend model was used to understand the nature of changes in the prices of the selected commodities and to make short-term forecasting. The model revealed a different pattern of price change for different commodities in both wholesale and retail markets. In case of mutton, egg (chicken), egg (duck), beef, and silver carp fish, it was highly upward sloping which indicates that price of these commodities will increase at an increasing rate in the upcoming years. A moderately increasing rate of price change was observed for katla fish in both the markets while for broiler, indigenous chicken and rohu fish, it was found a downward sloping. On the contrary, the projection indicates that the price of tilapia fish would remain stable in the near future. Such a scenario suggest that market monitoring system should be strengthened by the government to control the extreme increase or decrease in prices so that none of the stakeholders would be the gainer nor looser from the pricing policy in Bangladesh.Ann. Bangladesh Agric. (2020) 24(1) : 99-112